Fatal Campylobacter jejuni infection in a patient splenectomised for thalassaemia. Issue 5 (May 1997) - Jackson, N; Zaki, M; Rahman, A R; Nazim, M; Win, M N; Osman, S
Abstract : A 35 year old man with a fatal Campylobacter jejuni infection is described. He had HbE/beta zero thalassaemia and had undergone splenectomy nine months previously for hypersplenism; he also had chronic hepatitis C infection. He presented with high grade fever but no gastrointestinal symptoms and rapidly progressed to septicaemic shock and hepatic encephalopathy despite treatment with penicillin, gentamicin, and, later, chloramphenicol and ceftazidime. Only one case of Campylobacter jejuni septicaemia occurring post-splenectomy has been reported previously, also in an iron overloaded thalassaemia patient. Unusual Gram negative bacilli must be covered by the chosen antibiotic regimen when splenectomised thalassaemic patients present with high grade fever.